Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

Encapsulated tannic acid protects against ETEC-induced intestinal damage via modulating gut microbiota and barrier function - Hang Gao; Ying Xiao; Tianjiao Wang; Ruohan Liu; Qiao Li (Food Research International, 2026)

Performance of micro-nanobubbles for synergistic control of ultrafiltration membrane fouling and emerging contaminants during nutrient recovery from biogas slurry - Wancen Liu; Ruohan Xia; Chuanren Qi; Yun Li; Guo Wei; Guoxue Li; Long D. Nghiem; Wenhai Luo (Chemical Engineering Journal, 2026)

Integrated metagenomics unravels the microbial mechanisms driving greenhouse gas and odor emissions during composting - Ruohan Xia; Bin Cui; Guoxue Li; Haibin Zhou; Wenhai Luo; Zhicheng Xu (Bioresource Technology, 2026)

Mg/Fe-layered double hydroxide-loaded biochar enhances nitrogen retention and reduces geochemically reactive metal concentrations in paddy soil: Bacterial community responses - Hengxin Liu; Ruohan Li; Yueming Han; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

Signal competition versus metabolic inhibition: Divergent fates of antibiotic resistance genes under N-acyl-L-homoserine lactone-targeted quorum quenching in composting - Ruohan Xia; Tong Shi; Jirong Zhao; Guoxue Li; Wenhai Luo; Zhicheng Xu (Journal of Hazardous Materials, 2026)

A progressive physics-informed neural network method for porosity evaluation: a case study of the Qiongzhusi Formation shale - Pan Zhang; Benqi Zhang; Ruohan Shi; Zilong Ren; Yanghu Li; Weibiao Xie (Journal of Applied Geophysics, 2026)

Emulsion gels stabilized by millet chaff prolamin–gallic acid or –sucralose conjugates: characterization, application in curcumin, and mechanism insights - Yan Li; Jie Liu; Hao Wang; Biao Ma; Zihao Zhang; Ling Dang; Yajun Zheng; Ruohan Liu; Yi Li (Food Chemistry, 2026)

Toxoplasma gondii infection reduces CD59 expression through downregulation of JAK2/STAT3 signaling axis to enhance decidual NK cell cytotoxicity via the RAS/MAPK pathway - Shuyan Wang; Luyun Huo; Yan Zou; Ruohan Yang; Xiao Wang; Haixia Zhang; Liqin Ren; Jing Yang; Jie Li; Xuemei Hu; Yushan Ren (Inflammation Research, 2026)

Effect of starches on the preparation and properties of special low-protein scones - Ruohan Li; Ye Zi; Cuiping Shi; Wei Cai; Jian Zhong (Food Chemistry, 2026)

Cellulose-based adhesives: From molecular mechanisms to emerging applications - Shijie Du; Guangyi Li; Yixin Zhu; Yingxuan Shi; Ruohan Cao; Suiyi Li; Changlei Xia (Chemical Engineering Journal, 2026)

Combined organic pollutants and heavy metals distinctly alter microbial assembly and metabolism of Cynodon dactylon (L.) Pers. within industrial green belts - Junyi Yu; Shuangqiang Li; Junru Guo; Ruohan Huang; Chen Cai; Kaiming Peng; Lijun Lu; Xiangfeng Huang; Jia Liu (Journal of Environmental Sciences, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Chemical reaction kinetics regulated dual-signal sensing system for discriminating EV-A71 and CV-A16 - Tongtong Ye; Wenjing Xu; Ruohan Tang; Yuhan Wang; Yang Li; Xuming Zhao; Hui Zhang; Lihua Chen (Analytica Chimica Acta, 2026)

Regulating bulk density to harness microbial dynamics to enhance humification in food waste digestate composting - Xingzu Gao; Ruohan Xia; Zhicheng Xu; Feiyu Yang; Jingwen Cheng; Chuanren Qi; Guoxue Li; Wenhai Luo (Journal of Environmental Chemical Engineering, 2026)

Comprehensive evaluation of Ganoderma lucidum extracts: digestion kinetics, gut microbiota modulation, and immunoregulatory mechanisms - Tianjia Jiang; Rongye Zhu; Xiuliang Guo; Jian Li; Xuan Zhu; Ruohan Bao; Jie Chen (Food Research International, 2026)

Metal-free C H functionalization unlocks multifunctional luminescent PEGs for biomedical imaging and therapy - Weiping Liu; Qinyue Guo; Lifang Ma; Ruohan Li; Jiajia Ren; Haixia Jiang; Gang Wang; Rong Zeng (Chemical Engineering Journal, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

Genome-resolved metagenomic insights into cornstalks-mediated reduction of pathogens and antibiotic resistomes during passively aerated static composting of swine manure - Ruohan Xia; Tong Shi; Wancen Liu; Guoxue Li; Suli Zhi; Wenhai Luo; Zhicheng Xu (Journal of Environmental Management, 2026)

Conversion of wheat straw by black soldier fly larvae and fertilization effects of frass - Xifeng Wang; Ruohan Wang; Junzhao Wei; Rui Hu; Ziling Wang; Haifeng Li; Pengxiao Chen; Jianhang Qu; Mingjun Li (Journal of Asia-Pacific Entomology, 2026)

A small technology for big health: Blocking the potential spread of antibiotic resistomes from home composting of food waste by mature compost - Ruohan Xia; Lanxia Zhang; Guoxue Li; Wenhai Luo; Zhicheng Xu (Waste Management, 2026)

Levels and associated potential ecological risks of heavy metals in surface sediments from wetlands in the western Yellow River Delta - Ruohan Zhang; Zaiwang Zhang; Junxia Yang; Xu Zhang; Shanshan Liu; Jianchao Jin; Guangwu Liu; Changqing Shan; Jian Li; Jianhui Tang (Regional Studies in Marine Science, 2026)

Gallic acid-reinforced Rana chensinensis ovum protein isolates-Gellan gum thermally reversible emulsion gel: Insight of the structure and potential applications in dysphagia management - Ruixue Liu; Min Gao; Li Zhang; Shihan Wang; Ying Yang; Jing Bai; Ruohan Wang; Yongsheng Wang; Zhihan Wang (Food Research International, 2025)

A nanofiltration and electrocatalytic membrane reactor with ozone oxidation integrated system for dyeing wastewater treatment and Na2SO4 recovery - Minghui Du; Ruohan Wang; Hong Wang; Jianxin Li (Water Research, 2025)

Accurate identification and formation mechanism unraveling of radicals in UV-induced peracetic acid activation system using in-situ electron paramagnetic resonance - Long Chen; Ruohan Zhang; Zhaoli Liu; Fan Li; Boyu Huang; Wen Liu (Science Bulletin, 2025)

Integrative N-glycomics and N-glycoproteomics landscape reveals up-regulation of complex-type N-glycosylation in the tolerance of peach fruit to chilling injury - Huiwen Wang; Tonghao Cui; Jiaqi Wang; Ruohan Ou; Yilong Liu; Bo Zhang; Changjie Xu; Changqing Zhu; Miaojin Chen; Yanna Shi; Yuanjiang Pan; Kunsong Chen; et al. (Postharvest Biology and Technology, 2025)

Graft copolymerization synthesis of chitosan-polyferric sulfate composite coagulant to improve biogas slurry treatment toward effective irrigation - Ruohan Xia; Wancen Liu; Long D. Nghiem; Dingge Cao; Guoxue Li; Wenhai Luo (Journal of Environmental Management, 2025)

Temporomandibular joint CBCT image segmentation via multi-view ensemble learning network - Piaolin Hu; Jupeng Li; Ruohan Ma; Kai Zhang; Yong Guo; Gang Li (Medical & Biological Engineering & Computing, 2025)

Corrigendum to “Distribution characteristics, risk assessment, and quantitative source apportionment of typical contaminants (HMs, N, P, and TOC) in river sediment under rapid urbanization: A study case of Shenzhen river, Pearl River Delta, China” [Process Saf. Environ. Prot. 162 (2022) 155–168] - Ying Zhang; Wei Mao; Ruohan Li; Yang Liu; Peng Wang; Zelin Zheng; Yuntao Guan (Process Safety and Environmental Protection, 2025)

Paper strips-based narrowing colorimetry: An all-in-one strategy for rapid visual detection and adulteration identification of food dyes - Shuangshou Wang; Haiyang Li; Tong Li; Ruohan Xu; Chunyan Yang; Tianyou Geng; Tingxuan Yan; Qi Zhang; Daojin Li; Jingchong Yan; Yanshang Kang; Caibo Yue (Food Control, 2025)

Lab on a single microbead: An enzyme-free strategy for the sensitive detection of microRNA via efficient localized catalytic hairpin assembly - Yan Qi; Jiangtao Yu; Ming Lou; Yameng Yu; Ruohan Li; Zhenhao Zhang; Yuxuan Dai; Kejing Lao; Meng Cao; Xingchun Gou (Analytica Chimica Acta, 2025)

First retrieval of 24-hourly 1-km-resolution gapless surface ozone (O3) from space in China using artificial intelligence: Diurnal variations and implications for air quality and phytotoxicity - Fan Cheng; Zhanqing Li; Zeyu Yang; Ruohan Li; Dongdong Wang; Aolin Jia; Ke Li; Bin Zhao; Shuxiao Wang; Dejia Yin; Shengyue Li; Wenhao Xue; et al. (Remote Sensing of Environment, 2025)

Generation of advanced glycation end products from glycated protein or fructose/glyoxal-protein adducts under in vitro simulated gastrointestinal digestion - Xiaojin Yuan; Shuqing Feng; Jianuo Li; Ruixin Guo; Chenxi Nie; Ruohan Zhai; Aobai Tu; Xinyu Cao; Min Zhang; Juxiu Li (Food Chemistry, 2025)

A novel approach to estimate land surface temperature from landsat top-of-atmosphere reflective and emissive data using transfer-learning neural network - Shuo Xu; Dongdong Wang; Shunlin Liang; Aolin Jia; Ruohan Li; Zhihao Wang; Yuling Liu (Science of The Total Environment, 2024)

Joint probabilistic risk of organic micropollutants in the aquaculture seawater around Liaodong Peninsula - Yongle Zhu; Ruohan Zhang; Huaijun Xie; Lingyun Mo; Jingwen Chen; Kiwao Kadokami; Xuehua Li (Science of The Total Environment, 2024)

The impact of population change on social-ecological systems’ vulnerability: A case of the Qinling-Daba Mountains of Southern Shaanxi in China - Runyang Li; Jia Chen; Xinjun Yang; Sha Yin; Ruohan Shi; Yuling Bai; Li Xu (Journal of Cleaner Production, 2024)

Photoexcitation-induced efficient detoxification and removal of arsenite in contaminated water by a layered double hydroxide-supported polyacrylate stabilized ferrous sulfide composite - Wei Mao; Yibing Li; Lixun Zhang; Xuewu Shen; Yang Liu; Ruohan Li; Yuntao Guan (Journal of Hazardous Materials, 2024)

A novel chitosan and polyferric sulfate composite coagulant for biogas slurry pretreatment by simultaneous flocculation and floatation: Performance and underlying mechanisms - Ruohan Xia; Wancen Liu; Long D. Nghiem; Dingge Cao; Yun Li; Guoxue Li; Wenhai Luo (Water Research, 2024)

Covalent organic framework with donor-acceptor structure for rapid and sensitive photothermal sensing detection - Zhen Zhang; Zhenkai Hao; Ruohan Yang; Ruiping Shan; Xiangyang Li; Hongyan Zhang (Food Chemistry, 2024)

Shaking table tests on deformation pattern and failure mechanism of fault-crossing tunnels in non-rupture scenario - Ruohan Li; Xu Zhao; Emilio Bilotta; Jinghua Zhang; Mi Zhao; Jingqi Huang; Yong Yuan (Soil Dynamics and Earthquake Engineering, 2024)

Overexpression of MrMYB12 or MrMYB12/MrF3’5’H results in flavonol-rich tomato fruit that improves resistance against Botrytis cinerea during the shelf life period - Yunlin Cao; Ruining Zhang; Ruohan Ou; Yuyang Mei; Xiangrui Cui; Tong Zhang; Xiaochun Yang; Yanna Shi; Xiaoyong Zhao; Changjie Xu; Kunsong Chen; Xian Li (Postharvest Biology and Technology, 2024)

One-step process for debromination and mineralization of tetrabromobisphenol a by a layered double oxide-supported sulfurized nanoscale zero-valent iron under ambient conditions - Ruohan Li; Lixun Zhang; Ying Zhang; Zhengfang Zhang; Yuntao Guan (Chemical Engineering Journal, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Peridynamics-based large-deformation simulations for near-fault landslides considering soil uncertainty - Ruohan Wang; Shaofan Li; Yong Liu; Xuan Hu; Xin Lai; Michael Beer (Computers and Geotechnics, 2024)

Icaritin activates p53 and inhibits aerobic glycolysis in liver cancer cells - Xiangyang Zhou; Di Wu; Tian Mi; Ruohan Li; Tao Guo; Wenjuan Li (Chemico-Biological Interactions, 2024)

Effects of tree density variations on outdoor heritage conservation: Numerical study of an ancient brick city wall with four orientations - Ting Zhang; Changchang Xia; Yan Ma; Ruohan Zhang; Shuai Han; Zhenyi Kong; Shuichi Hokoi; Yonghui Li (Building and Environment, 2024)

Cloud detection from Himawari-8 spectral images using K-means++ clustering with the convolutional module - Kaizheng Wang; Yitong Fu; Shunzhen Zhou; Ruohan Zhou; Gang Wen; Fangrong Zhou; Lulu Li (International Journal of Remote Sensing, 2024)

Identification of novel umami peptides from yeast extract and the mechanism against T1R1/T1R3 - Hao Wang; Wenjun Wang; Shuyu Zhang; Zhenhao Hu; Ruohan Yao; Hadiatullah Hadiatullah; Pei Li; Guozhong Zhao (Food Chemistry, 2023)

Long-term exposure to the components of fine particulate matters and disability after stroke: Findings from the China National Stroke Screening Surveys - Hong Lu; Ruohan Wang; Jiajianghui Li; Mingkun Tong; Man Cao; Hengyi Liu; Qingyang Xiao; Yixuan Zheng; Yuanli Liu; Tianjia Guan; Tao Xue (Journal of Hazardous Materials, 2023)

Stillbirths attributable to open fires and their geographic disparities in non-Western countries - Tao Xue; Jiajianghui Li; Mingkun Tong; Xinguang Fan; Pengfei Li; Ruohan Wang; Yanshun Li; Yixuan Zheng; Jiwei Li; Tianjia Guan; Tong Zhu (Environmental Pollution, 2023)

High dimethylsulfoniopropionate concentrations in the surface seawater over the marginal seas of China and the Northwest Pacific Ocean during May–July of 2021 following La Niña - Lingxiao Li; Zhengguo Cui; Keming Qu; Hongsheng Wang; Ruohan Song; Xiaoke Hu; Shenghui Zhang; Tao Jiang; Mingying Zhou; Qingjing Hu (Marine Pollution Bulletin, 2023)

Comparison between deep learning architectures for the 1 km, 10/15-min estimation of downward shortwave radiation from AHI and ABI - Ruohan Li; Dongdong Wang; Shunlin Liang (Remote Sensing of Environment, 2023)

DEM investigation of the mechanical behavior of frozen soil along various stress paths - Ruohan Sun; Run Liu; Huan Zhang; Chun Liu; Chengfeng Li (Bulletin of Engineering Geology and the Environment, 2023)

Activation persulfate for efficient tetrabromobisphenol A degradation via carbon-based materials: Synergistic mechanism of doped N and Fe - Zhengfang Zhang; Yang Liu; Ying Zhang; Ruohan Li; Yuntao Guan (Journal of Hazardous Materials, 2023)

Occurrence and fate of antibiotics in swine waste treatment: An industrial case - Wancen Liu; Yongfang Wang; Ruohan Xia; Xiangrui Ding; Zhicheng Xu; Guoxue Li; Long D. Nghiem; Wenhai Luo (Environmental Pollution, 2023)

Local site effect of soil-rock ground: 1-g shaking table test - Yong Yuan; Siming Li; Haitao Yu; Mingqing Xiao; Ruohan Li; Ruozhou Li (Bulletin of Earthquake Engineering, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Comparison of pharmacokinetics, biodistribution, and excretion of free and bound Nε-carboxymethyllysine in rats by HPLC–MS/MS - Xiaojin Yuan; Ruohan Zhai; Yanan Bai; Min Zheng; Xiaoqing Xie; Tao Chen; Ting Huang; Zhifei Chen; Juxiu Li (Food Research International, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

Characteristics and Cause Analysis of Variations in Light Precipitation Events in the Central and Eastern Tibetan Plateau, China, During 1961–2019 - Kaifang Li; Liguo Cao; Zhengchao Zhou; Lei Jiao; Ning Wang; Ruohan Liu (Chinese Geographical Science, 2022)

Constant hypoxia inhibits osteoclast differentiation and bone resorption by regulating phosphorylation of JNK and IκBα - Zhenzhen Ma; Ruohan Yu; Jinxia Zhao; Lin Sun; Leilei Jian; Changhong Li; Xiangyuan Liu (Inflammation Research, 2019)

The Protective Effect of Selenium on the Chicken Pancreas against Cadmium Toxicity via Alleviating Oxidative Stress and Autophagy - Ruohan Liu; Tiantian Jia; Yuan Cui; Hongjin Lin; Shu Li (Biological Trace Element Research, 2018)